I. 2^{(x+2)}+ 2^{(-x)}=5

II. (1/(y+1)+ 1/(y+5))=(1/(y+2)+ 1/(y+4))

2^{(x+2)}+ 2^{(-x)}=5 2^{x} ×2² + 1/2^{x} - 5=0 Put 2^{x} = a We get 4a+ 1/a- 5=0 4a²+1-5a=0 4a²-4a-a+1=0 (4a-1)(a-1)= 0 a=1,1/4 If 2^x=1 x=0 2^x=1/4 If, 2^x=1/2² x= -2 (1/(y+1)+ 1/(y+5))=(1/(y+2)+ 1/(y+4)) (1/(y+1)- 1/(y+4))=(1/(y+2)- 1/(y+5)) (y+4-y-1)/(y+1)(y+4) = (y+5-y-2)/((y+2)(y+5)) 3/(y+1)(y+4) = 3/((y+2)(y+5)) 1/(y+1)(y+4) - 1/((y+2)(y+5))=0 ((y+2)(y+5)- (y+1)(y+4))/((y+1)(y+4)(y+2)(y+5))=0 y²+7y+10-(y^2+ 5y+4)=0 y²+7y+10-y²-5y-4=0 2y+6=0 y= -3 Hence, x>y

- I.12a
^{2}– 55a + 63 = 0 II. 8b^{2}- 50b + 77 = 0 - I. 5x² -14x + 8 = 0 II. 2y² + 17y + 36 = 0
- I. x
^{2}– 10x + 21 = 0 II. y^{2}+ 11y + 28 = 0 - I. 4p² + 17p + 15 = 0 II. 3q² + 19q + 28 = 0
- I. 3p² - 17p + 22 = 0 II. 5q² - 21q + 22 = 0
- I. 2x² - 11x + 12 = 0 II. 12y² + 29y + 15 = 0
- I. 3p² - 11p + 10 = 0 II. 2q² + 13q + 21 = 0
- I. 12y
^{2}+ 11y – 15 = 0 II. 8x^{2}– 6x – 5 = 0 - Roots of the quadratic equation 2x
^{2}+ x – 528 = 0 is - I. 6x² - 13 x + 6 = 0 II. 15 y² + 11 y - 12 = 0

More Quadratic equation Questions

×